2018
DOI: 10.1002/cpe.4902
|View full text |Cite
|
Sign up to set email alerts
|

A survey of real‐time capabilities in functional languages and compilers

Abstract: Functional programming languages play an important role in the development of correct software systems. As embedded devices become pervasive and perform critical tasks in our lives, their reliability becomes paramount. This presents a natural opportunity to explore the application of functional programming languages to systems that demand highly predictable behavior.In this paper, we explore existing functional programming language compilers and their applicability to real-time embedded systems. We do this by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 124 publications
(176 reference statements)
0
3
0
Order By: Relevance
“…Preempting the GC when it runs out of time could make it real-time compatible, but this will not suffice as collection could then not be guaranteed to always complete. This could be addressed by implementing incremental collection strategies (Nettles & O'Toole, 1993). The multiple GC strategies utilized by MLton further complicates the case by making the maximum pause time more unpredictable, as the strategy used for collection depends on the state of the heap when a collection is triggered.…”
Section: Consequences For Real-time Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preempting the GC when it runs out of time could make it real-time compatible, but this will not suffice as collection could then not be guaranteed to always complete. This could be addressed by implementing incremental collection strategies (Nettles & O'Toole, 1993). The multiple GC strategies utilized by MLton further complicates the case by making the maximum pause time more unpredictable, as the strategy used for collection depends on the state of the heap when a collection is triggered.…”
Section: Consequences For Real-time Systemsmentioning
confidence: 99%
“…Other languages with real-time capabilities: Our survey of existing functional languages and their real-time adaptability (Murphy et al, 2019) showed us that most languages we reviewed were found to be lacking in at least one of the key areas we identified in order to provide a predictable runtime system. However, some functional DSLs were found to be very suitable for hard real-time applications.…”
Section: Region-based Memory Managementmentioning
confidence: 99%
See 1 more Smart Citation